Efeito do treinamento concorrente e do destreinamento sobre a pressão arterial de mulheres hipertensas - Ramos, Ayrton Moraes (2015)
Few studies have investigated the effect of the Concurrent Training (CT) on blood pressure, either, the detraining consequences of this variable, especially in hypertensive individuals. Therefore, this study aimed to analyze the blood pressure values of hypertensive women, before and after 12 weeks of Concurrent Training and after 8 weeks of detraining, submitted to two different TC programs [weight lifting/walking (MC) and walking/ weight lifting (CM)]. Voluntarily participated 40 hypertensive women (56.0 ±5.2 years), which were divided into two groups: MC (n=20) and CM (n=20). Differences were observed (p≤0.05) for SBP and DBP between MC and CM in pre-training moment, which were used as covariates in other analyzes. Already in the MC group, there was difference (p≤0.05) between the post and the pre and detraining moments. In the CM group, differences (p≤0.05) occurred between the post and the pre moment. Only the MA group showed difference (p≤0.05) for the PAD values among the post and pre-training moments. As for DP values, the post and pre-training and detraining moments have been differenced (p≤0.05), only in the MC group. The Concurrent Training, following weight lifting and walking, has greater benefits, especially for high blood pressure in hypertensive individuals, and these are sustained even after 8 weeks of detraining.